Land Use Land Cover (LULC) Change Projection in Kathmandu Valley using the CLUE-S Model - Lamichhane, Suraj; Shakya, Narendra Man (Journal of Advanced College of Engineering and Management, 2021)
In the past few decades the urbanization pattern of the Kathmandu valley has rapidly increased and the process was sensed through the increase in the urban facilities, population growth, and changed LULC pattern. The historical LULC change was analyzed using the generated map and the future scenario was found through the CLUE-S LULC change model and processed in GIS environment. Five scenarios and nine driving forces were considered for the sensitivity and future analysis of the model. Based on the evaluation of the historical maps and the conservation matrix, the built-up area is found to be increased nearby by 5% and the agricultural area decreased by 6.5% during 2010 to 2018. It is concluded that the normal LULC conservation scenario provides more reliable information for the future projection. The simulation result highlights that nearly 4 km2 of fertile and open area will be converted to built-up areas due to the rapid urbanization per decade. This increase in urbanization process leads to more challenges in urban environment management in future.